Do Economic Changes Affect the Political Preferences of Arabs in Israel? - Sami H. Miaari; Amit Loewenthal; Wifag Adnan (Institute of Labor Economics (IZA), 2022)
We examine the relationship between socio-economic characteristics and voting patterns among Arabs in Israel. We combine panel data on 73 Arab localities with election results and socio-economic indicators for seven election years between 1996 and 2015. Exploiting variation in political preferences and socio-economic status between localities across time, we find that both demographic transition and improvements in standards of living are associated with a decrease in the proportion of Israeli Arabs voting for Jewish-majority parties and a rise in their electoral support for Arab Parties. We also find that the decrease in voter turnout among Arabs following the political effects of the Second Intifada may have been only circumstantial. Our results suggest that Arabs in Israel are becoming more politically independent, as a result of social, political and economic modernization.
Keywords: D01; 330; Israel; elections; Arabs; political economy